PENGARUH ONLINE ADVERTISING TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH FLOW EXPERIENCE DAN ADVERTISING VALUE PADA PRODUK SMARTPHONE VIVO - Puji Rahayu; Rizki Amalia (Departemen Manajemen, 2022)
This study aims to measure the effect of online advertising on purchase intention interestmediated by flow experience and advertising value on Vivo smartphone products in the city ofTakengon. The sample used in this study was Vivo smartphone users, totaling 200 respondents.Data collection equipment used in this study is a questionnaire. The sampling technique used ispurposive sampling. Structural Equation Modelling (SEM) is used as an analytical method todetermine the effect between the variables involved. Based on the results of SEM analysis identifiedthat online advertising has a positive effect on purchase intention, online advertising has a positiveeffect on flow experience, online advertising has a positive effect on advertising value, flowexperience has a positive effect on purchase intention, advertising value has a positive effect onpurchase intention, flow experience can mediate the relationship between online advertising andpurchase intention, and advertising value can mediate the relationship bertween online advertisingand purchase intention.